The structure of the Earth’s crust of the central part of the Holovanivsk suture zone according to the reinterpretation of materials of IV geotraverse of DSS (PK 295—400) - O. A. Trypolsky; O. V. Topoliuk; O. B. Gintov (Геофизический журнал, 2019)
The paper presents the results of reinterpretation of the materials obtained as a result of studies using the DSS method along the IV geotraverse at the site PK 295—400. The reinterpretation was carried out purposefully to clarify the seismic cross section in the area of the Holovanivsk gravity maximum (PK 320—360). A number of seismic sites and diffraction points were additionally identified in the crust at the depths of 2—60 km, which made it possible to form an objective idea of the deep structure of the considered part of geotraverse. The observations were carried out according to the method of continuous profiling, which provided for the registration of a system of direct and inverse hodographs of the main waves, linked at the inter-points. Compared to previous interpretations, the cross-section of the crust was significantly specified. The identification of additional diffraction points and a large number of short reflecting elements at the depths of 2—8 km made it possible to clarify the position of snaps in the cross section of the Talnivska zone. A series of short steeply inclined reflecting elements was identified in the central part of the cross-section (PK 338—355) at the depth of 8—26 km. Together with horizontally and obliquely lying elements (at the depth of 2—9 km and 24—44 km), they form an environ area that differs according to its features from the host rocks at the depth of 2—44 km, which made it possible to retrace the listric shear zone that continuously extends from the depth of 8 km at PK 355 to 44 km at PK 304. Taking into account the seismic tomographic data, it was suggested that the Talnivska zone of snaps can be retraced to the depth of 100—600 km as a boundary between blocks with different velocities VP and steps and breaks in the Golitsyn—Geyko layer. Close by the daylight surface, the listric shear zone is connected to the main part of the Talnivska fault zone. According to the latest version of the reinterpretation of the DSS data, the feeder of the intrusive body of hyperbasites is quite narrow at the depth of 60—33 km and expands to a thickness of about 15 km only starting from 30 km and almost to the body surface. This is precisely the width of the hyperbasites outbreaks onto the surface of the crystalline basement in the area to the south of the IV geotraverse. Focusing on the area of relatively high velocities VP at the depth of 2—33 km, it can be assumed that the main body of the intrusion of hyperbasites and basit-dunites, peridotites, pyroxenites, gabbro and amphibolites, the density of which exceeds the density of the host rocks by 0.1—0.22 g/cm3, is located particularly at these depths along the axis of the central part of the Holovanivsk suture zone.